Maqasidi Leadership of Minority Religions Figure for Maintaining Tolerance in Manado, Indonesia - Ismail, Feiby; Arifin, Zainal; Rahmi, Sri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
Manado's Muslim minority mindset stops social, political, and religious activities. Although Islam is the second-largest religion after Protestantism, this mindset can be seen by the impression that Manado is a 'Christian City' known as the “Tower of a Thousand Churches.” This article describes the strategy of minority religious leaders (Islam) in tolerating the perspective of Maqasid al-Syari'ah. The research data was collected through observation and in-depth interviews with religious leaders from the Islamic boarding school Kiai, IAIN Manado lecturers, and Muslim youth. The research findings show that first, the values ​​of religious tolerance in Manado have developed in the form of slogans, such as